IMPACT OF ENTREPRENEURSHIP EDUCATION ON POLYTECHNIC STUDENTS’ INCLINATION TO ENTREPRENEURIAL PRACTICE IN NIGERIA - Yusuf Alhaji Hashim; Mohammed Abdulmalik; Wanjuu Lazarus Zungwe (Malete Journal of Accounting and Finance)
In Nigeria, entrepreneurship education in higher institutions of learning was introduced with the aim of inculcating entrepreneurial skills and attitudes in students to motivate them to take up entrepreneurship as a career. However, despite the introduction of entrepreneurship education as a core course in these institutions, the aspirations for white collar jobs by graduates continues which has resulted in the persistent increase in the rate of unemployment. This study examined the impact of entrepreneurship education on polytechnic student’s inclination to entrepreneurial practice, with special reference to Kaduna Polytechnic, Kaduna State. The study used survey research design and primary data were collected using questionnaire. Data collected were analysed using Minitab version 16.0. The study found that students with knowledge of entrepreneurship are more inclined to entrepreneurial practice, with male students more inclined to becoming entrepreneurs than female students. Therefore, the study recommended that students be given more exposure to entrepreneurship education in order to develop the entrepreneurial knowledge and skills to reduce graduate unemployment in Nigeria.